Trade policies for improved food security - Melagne, N'Guessan Dieu-Donne; Ehuitche, Beke Tite (International Food Policy Research Institute, 2021)
Africa south of the Sahara (SSA) remains highly dependent on agricultural and food trade for its population’s wellbeing (Bouët et al, 2021). In particular, regional trade integration is crucial for food security in the region, where agricultural trade plays an essential role in regulating the supply and prices of food products and contributes to household food security. Food and nutrition security are among the main priorities established by SSA’s major regional integration agreements, including ECOWAS/ECOWAP; ECCAS/SAC; COMESA, and the AfCTA (CEDEAO, 2015; Matthews, 2003; AEC, 2018). Despite existing free trade agreements for agri-food products within regional areas, however, many trade barriers remain: weak transport and communication infrastructures, technical barriers to trade, abusive controls and illicit payments from corridors, costs and delays of customs procedures, information and exchange costs, and costs linked to local distribution and pricing of agri-foodstuffs. These barriers are also combined with the region’s current structural and institutional weaknesses. To tackle these obstacles and improve food security, appropriate actions and policies are required (Tinta et al., 2018; N’guessan et Béké, 2020). This proposal outlines specific recommendations for best practices in trade facilitation and related policies for improved food security in SSA countries, based on relevant recent research.